Acculturative Stress, Anxiety Sensitivity, and Smoking among Spanish-Speaking Latinx Adult Smokers. (15th April 2020) - Zvolensky, Michael J.; Shepherd, Justin M.; Bakhshaie, Jafar; Peraza, Natalia; Garey, Lorra; Mayorga, Nubia A.; Berger-Cardoso, Jodi
Abstract: Objectives: Although acculturative stress is a known individual difference factor related to poor health, little is understood about its relationship to smoking among Latinx adults. One transdiagnostic factor that may serve a mediational role in the relation between acculturative stress and smoking is anxiety sensitivity. The current study evaluated whether anxiety sensitivity mediated the relations between acculturative stress and smoking among a large sample of adult Spanish-speaking Latinx smokers. Method: Participants were 359 Spanish-speaking Latinx daily smokers (58.8% female, M age = 33.2 years, SD = 9.7) who provided self-report data on acculturative stress, anxiety sensitivity, and smoking outcomes of cigarette dependence, perceived barriers for quitting cigarettes, and severity of problems during past quit attempts. Independent mediation models were conducted for each smoking outcome, with acculturative stress entered as the predictor and anxiety sensitivity entered as the proposed explanatory factor. Results: There were statistically significant indirect effects of acculturative stress via anxiety sensitivity in relation to cigarette dependence, perceived barriers for quitting cigarettes, and severity of problems during past quit attempts. Conclusions: The present findings provide novel evidence that anxiety sensitivity serves a mediational role in relations between acculturative stress and smoking outcomes among Latinx adult smokers.